Analysis of Determinant Factors Affecting Women's Income in the Seaweed Industry in Pantai Amal, Tarakan City - Kartini, Kartini; Rahmatullah, Dedy; Islami, Rahmi Nur (Perkumpulan Dosen Muda (PDM) Bengkulu, 2025)
Income is one of the indicators used to achieve or improve community welfare. Low household income often necessitates women taking on a role in fulfilling financial needs. This study aims to identify and analyze the partial effects of age, number of family dependents, working hours, and length of employment on the income of female seaweed workers, as well as to analyze the simultaneous effects of these factors on their income. The study was conducted in Pantai Amal Subdistrict, Tarakan City. The sampling method used was non-probability sampling, with a total of 68 samples determined using the Lemeshow formula. The analysis applied in this study includes classical assumption tests and multiple linear regression analysis. The results of this study conclude that, based on the t-test, the number of family dependents (t-value: 3.054, significance: 0.003), working hours (t-value: 2.550, significance: 0.013), and length of employment (t-value: 2.315, significance: 0.033) have a significant effect on the income of female seaweed workers. Furthermore, age, number of family dependents, working hours, and length of employment simultaneously have a significant effect on their income, with an F-value of 5.332 and a significance value of 0.001